Under Childrens Eyes: Becoming Pious in Tayeb Salih and Pramoedya Ananta Toer Short Stories - Dewi, Novita (Al-Jamiah: Journal of Islamic Studies, 2017)
This research seeks to discuss how child characters navigate their interactions with the adults in two short stories set in the predominantly Islamic society of Sudan and Indonesia. It examines Tayeb Salihâs âA Handful of Datesâ (1964) and Pramoedya Ananta Toerâs âCircumcisionâ (1950) by locating both texts in World Literature which is largely Western or Eurocentric. Both short stories belong to the genre of initiation fiction often included in world literature anthologies. This paper argues that both authors help contribute to not only the rethinking of World Literature concept and circulation thereof, but also balanced view of heterogonous, multicultural Muslim society. Using post-Genette focalization theory as conceptual framework, this study finds out that the child narrators play distinct roles as (1) the perceptual focalizer to reveal injustice and frivolity of the adultsâ world; (2) the ideological focalizer to make meaning of childrenâs faith through their relationship with the grown-ups.Â [Penelitian ini bertujuan membahas bagaimana tokoh anak berinteraksi dengan orang-orang dewasa dalam dua cerita pendek dari negara berpenduduk mayoritas Islam, Sudan dan Indonesia. Karya Tayeb Shalih, "A Handful of Dates"[Segenggam Kurma] (1964) dan karya Pramoedya Ananta Toer "Sunat" (1950) dikaji dengan menempatkan kedua teks dalam Sastra Dunia yang cenderung berkiblat ke dunia Barat dan Eropa. Kedua cerita pendek Â bergenre fiksi inisiasi ini sering diikutkan dalam antologi sastra dunia. Makalah ini menunjukkan bahwa kedua penulis memberikan kontribusi dalam penafsiran ulang konsep dan peredaran Sastra Dunia, serta pandangan yang lebih seimbang terhadap masyarakat Muslim yang heterogen dan multikultural. Menggunakan Teori Fokalisasi Pasca-Genette sebagai kerangka konseptual, studi ini menyimpulkan bahwa tokoh anak dalam kedua cerpen memainkan peran yang berbeda sebagai (1) focalizer (penyuara) perseptif yang mengungkapkan ketidakadilan dan kedegilan dunia orang dewasa; (2) penyuara ideologis yang memaknai keimanan anak lewat relasi dengan orang-orang dewasa.]